Analisis Peningkatan Level Berpikir Geometri Mahasiswa Berdasarkan Teori Van Hiele dengan Pendekatan Konstruktivisme - Renanda, Aini; Qohar, Abd.; Chandra, Tjang Daniel (Jurnal Tadris Matematika, 2023)
The provision of problem-solving, analytical, systematic, critical, and creative skills is important to improve human resources that can be obtained from learning mathematics. Geometry is a field of mathematics that aims to develop logical thinking skills, develop spatial intuition, and interpret mathematical arguments. Several studies show that students' understanding of geometry material is still at a low level, so it is necessary to develop or improve the geometry learning process. The purpose of this study is to describe the increase in students' geometric thinking levels based on Van Hiele's theory with a constructivism approach. The method used in this research is descriptive qualitative with data analysis techniques using the Miles & Huberman model in the form of data reduction, data presentation, and drawing conclusions. The results showed that before the learning process using a constructivist approach, students' geometric thinking skills were at levels 1 to 3 or the analysis stage to a formal deduction with the average being at the informal deduction and pre-formal deduction stages. Meanwhile, after the learning process using a constructivist approach was carried out, geometric thinking skills increased at levels 2 to 4 or the informal deduction stage to the rigor with an average increase in the formal deduction stage.